Decontamination of Soil Contaminated with Cesium using Electrokinetic-electrodialytic Method. (1st November 2015) - Kim, Gye-Nam; Kim, Seung-Soo; Park, Uk-Rang; Moon, Jei-Kwon
Graphical abstract: Highlights: Removal efficiency of 137 Cs + by electrokinetic-electrodialytic was higher than electrokinetic. An anion exchange membrane shortened the period for removing cesium from the soil. The more the initial radioactivity of soil increased, the more the removal efficiency of Cs induced. The soil stirring accelerated the desorption of cesium ions from soil. Abstract: The soil contaminated with cesium was sampled at an area near a nuclear facility in Korea. Electrokinetic decontamination equipment and electrokinetic-elctrodialytic decontamination equipment were manufactured to decontaminate the contaminated soil. The removal efficiency according to the lapsed time by the electrokinetic decontamination equipment and the electrokinetic-elctrodialytic decontamination equipment was investigated through several experiments. The difference between the removal efficiency of the electrokinetic-elctrodialytic equipment without an anion exchange membrane and that with an anion exchange membrane was investigated through several experiments. The removal efficiency of 137 Cs + from soil by electrokinetic-electrodialytic decontamination technology was higher than that of 137 Cs + from soil by electrokinetic decontamination technology. The removal efficiency of 137 Cs + was sharply reduced after 7 days on using electrokinetic decontamination, because the 137 Cs + on the surface of the soil particles had almost been removed for 7 days. The removal efficiency of 137 Cs + was increased after 7 days on using electrokinetic-electrodialytic decontamination with soil stirring. The soil stirring accelerated the desorption of cesium ions from soil and an anion exchange membrane shortened the period for removing cesium from the soil cell by preventing the influx of cesium ions into the anode room. The more the initial radioactivity concentration of soil increased, the more the removal efficiency of 137 Cs + from soil increased. When the electrokinetic-electrodialytic decontamination period of 0.3–7.0 days elapsed, 137 Cs + in the soil was removed by about 12–83%. When the electrokinetic-electrodialytic decontamination period of 10–21 days elapsed, the 137 Cs + in soil was removed by about 91–97%.